Changes in Vitamin D Levels Following Climatotherapy at the Dead Sea - Shany, Shraga (Anales de Hidrología Médica, 2012)
Background: The Dead Sea region in Israel is the deepest spot on earth, 422 meter beneath sea level. The atmosphere layer overhanging this region is larger than in any other place on earth, allowing a filtration effect on sunshine beams and leading to their moderate attenuation in the Ultraviolet B (UVB) spectrum. The question was raised whether exposure to this sunshine may increase serum Vitamin D levels of patients treated at the Dead Sea. Objectives: To assess, in Norwegian patients suffering from joint disease and chronic pain syndromes, the magnitude of change in 25-Hydroxyvitamin D levels (25-OH-D) after Dead Sea Climatotherapy (DSC). Methods: 117 Norwegian patients received regular DSC procedures during their 3 weeks visit, which includes sun exposure (60 to 90 minutes), Dead Sea bath and outdoor physical activities. The cumulative solar UVB exposure was calculated in Minimal Erythema Doses (38.3 ±12.8 MEDs). Blood sampling for measurements of 25-OH-D levels were performed upon arrival and on the last day of their stay. Data were evaluated by statistical analysis using paired t test. Results: Following the DSC serum 25 OH Vitamin D levels were increased from 51.9 ± 2.7 nano mol per liter (nM), to 64.2 ± 3.1 nM  (p
Keywords: Musculoskeletal Diseases; Vitamin D; Dead Sea